"Emerging from the Shadows: New Developments in the History of Interracial Sex and Intermarriage in Colonial North America and the Caribbean". Issue 3 (March 2015) - Livesay, Daniel
Abstract: This article analyzes recent historical scholarship on cross‐racial pairings in colonial North America and the Caribbean. The degree of tolerance for these matches, as well as the accommodation of the mixed‐race children born from them, illuminates the contours and experiences of racial prejudice in this period. For many years scholars believed this to be primarily a phenomenon in Iberian colonies, and occasionally the French, with much work focusing on pairings between indigenous and European populations. However, recent scholarship has shown a greater degree of racial mixture in both the British and French colonies than once thought, even between African‐descended and European groups. This is especially true when the Caribbean is added to considerations of colonial attitudes. These developments open new doors into historical understandings of colonial race relations, slavery, and family compositions.